Unskilled blue collar workers: Bourgeois and/or authoritarian? Results from a small scale survey in Belgium - Hans De Witte (The Journal for Transdisciplinary Research in Southern Africa, 2007)
In this article, two contrasting theories on the attitudes of unskilled blue collar workers are confronted: the ‘embourgeoisement’ thesis and the hypothesis of the ‘authoritarianism of the working class’. The ‘embourgeoisement’ thesis states that blue collar workers adopted the attitudes (and life style) of white collar workers, from whom they can no longer be distinguished. Lipset’s hypothesis of the ‘authoritarianism of the working class’, on the other hand, states that blue collar workers more strongly endorse a conservative attitude on socio-cultural matters and a progressive stand concerning socio-economic issues. Both hypotheses are tested using data from a small scale survey (N = 135) among unskilled blue collar workers and lower- and mid-level white collar workers from different large companies in the region of Leuven, Belgium. The results indicate that the interviewed unskilled blue collar workers still hold a set of attitudes that distinguishes them from the interviewed white collar workers. So, the ‘embourgeoisement’ thesis was refuted. Instead, the unskilled blue collar workers were more conservative on a socio-cultural level, and more progressive concerning socio-economic issues. These results are in line with Lipset’s ‘authoritarianism of the working class’ hypothesis.